Helicobacter pylori‐induced YAP1 nuclear translocation promotes gastric carcinogenesis by enhancing IL‐1β expression. (30th May 2019) - Wu, Yujiao; Shen, Li; Liang, Xiuming; Li, Shuyan; Ma, Lin; Zheng, Lixin; Li, Tongyu; Yu, Han; Chan, Hillary; Chen, Chunyan; Yu, Jingya; Jia, Jihui
Abstract: Gastric cancer (GC) is one of the most common and malignant pathologies, and a significant portion of GC incidences develops from Helicobacter pylori (Hp) ‐induced chronic gastritis. Although the exact mechanisms of GC are complex and poorly understood, gastric carcinogenesis is a good model to investigate how inflammation and infection collaboratively promote tumorigenesis. Yes‐associated protein 1 (YAP1) is the key effector of the Hippo pathway, which is silenced in most human cancers. Herein, we verified the tumor‐promoting effect of YAP1 in vitro, in vivo, and in human specimens. We revealed that YAP1 displays nuclear translocation and works with TEAD to activate transcription of the crucial inflammatory cytokine IL‐1β in gastric cells infected with Hp . As IL‐1ß accounts for inflammation‐associated tumorigenesis, this process can lead to gastric carcinogenesis. Thus, in addition to activating proliferation genes, YAP1 also plays a major role in inflammation amplification by activating inflammatory cytokine genes. Excitingly, our research demonstrates that transfection of mutant plasmid YAP‐5SA/S94A or addition of the drug verteporfin, both of which are thought to disrupt the YAP1‐TEAD interaction, can arrest the carcinogenesis process. These findings can provide new approaches to GC treatment. Abstract : Helicobacter pylori induce YAP1 overexpression and nuclear translocation. YAP1 activates IL‐1ß transcription co‐working with TEAD. YAP1‐controlled IL‐1ß overexpression contributes to GC. YAP1‐TEAD interaction can be a drug target in GC treatment.